Prediction Model for Spontaneous Combustion of Coal around Boreholes Using Bedding Gas Drainage - Youxin Zhao; Qingjie Qi; Xinlei Jia (Shock and Vibration)
To accurately and reliably predict the time of spontaneous combustion of fractured coal around a borehole induced by gas drainage along the seam, this study performed an orthogonal test taking the No. 10 Coal Mine of Pingdingshan as the research object, in terms of the suction negative pressure and coal seam buried depth. COMSOL Multiphysics was used to model the orthogonal test results, and a multielement statistical analysis of four factors and their relationships with the spontaneous combustion of coal around the borehole and a single-factor analysis in line with the site conditions were performed on the modeling results through multiple regression. The results showed a nonlinear regression relationship between the sealing hole length, sealing hole depth, negative pressure, and coal seam depth and the spontaneous combustion of the coal around the gas drainage borehole; the prediction regression model is significant. Taking the field gas drainage in the No. 10 Coal Mine of Pingdingshan as an example, the relationship between the time of spontaneous combustion of gas drainage and the drainage pressure follows a power of two. When the drainage negative pressure is less than 45 kPa, the coal around the borehole is more likely to undergo spontaneous combustion with increasing pressure, and the sealing hole length has a positive linear correlation with the time of spontaneous combustion of the coal around the borehole. When the sealing hole length is 23 m, the time of spontaneous combustion of the coal around the gas drainage hole is >500 days, and the coal around the borehole does not easily undergo spontaneous combustion. When the sealing depth is 15 m, the time of spontaneous combustion of the coal around the gas drainage hole is 76 days, which is most likely to cause spontaneous combustion.